TINJAUAN YURIDIS TENTANG AKTA OTENTIK SEBAGAI ALAT BUKTI PERKARA PERDATA DI PENGADILAN NEGERI SAMARINDA - Dian Ariani (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT Notary Public is a public official who is appointed by law in making an authentic deed and at the same time a notary is an extension of the Government. authentic deed is a guarantee of certainty and legal protection as a concrete form of actions, events, and legal relations that occur in society. the purpose of this research is to find out the authentic deed proof in court and to know the legal consequences of the authentic deed containing false information. The benefits or uses of this research are in the form of theoretical and practical benefits.This research uses empirical legal research that examines the applicable legal provisions and what happens in reality in the community. Empirical juridical research is legal research on the application or implementation of normative legal provisions in action on any particular legal event that occurs in the community. Or in other words that is a study conducted on the actual situation or real conditions that occur in the community with a view to knowing and finding the facts and data needed, after the required data is collected then leads to the identification of problems that ultimately lead to problem solvingThe results of the study explained that the legal power of a notary deed in the process of proof in a court is perfect and binding, so that it does not need to be made or supplemented with other evidence, the deed still exists which is canceled is the contents of the deed (the legal relationship). As well as the legal consequences of an authentic deed containing false information is that the authentic deed has caused a dispute and is brought to court, therefore the injured party can file a civil suit in court so that the judge can decide and grant the cancellation of the deed. Keywords: Legal Consequences, Authentic Deed, Proof